2022
DOI: 10.1007/s40841-022-00254-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the “Three Steps in Screening for Dyslexia” Assessment Protocol Designed for New Zealand Teachers

Abstract: Traditionally, the New Zealand Ministry of Education opposed the recognition of dyslexia. However, since 2007, the Ministry of Education’s position has started to change, evidenced by the development of a working definition. In 2021 the Ministry of Education released Three Steps in Screening for Dyslexia (TSSD), an assessment protocol designed to support teachers to screen for dyslexia. The current research evaluated the TSSD with a sample of 209 children in Years 4 to 6 (8–10 years-of-age) from New Zealand. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The Woodcock-Johnson Tests of Cognitive Abilities is a valid and reliable instrument for assessing cognitive ability and achievement in children and adults, first introduced in 1977 by Richard Woodcock and Mary E. Bonner Johnson (Woodcock, 1997). In this study, the Woodcock-Johnson IV (WJIV) scale was used to assess children's Reading Comprehension and Language Comprehension as one of the criteria for determining whether a child had Dyslexia, in a study conducted by Sleeman and colleagues on 209 local New Zealand children (Sleeman et al, 2022). Raman and colleagues in order to study the assessment of Dyslexia in children in a multilingual environment, 46 native Indian children aged 8-13 years were selected to participate in the relevant test and Woodcock-Johnsonn III Tests of Academic Achievement were used as an instrument to assess SLD (including Dyslexia) and the results of the study showed the reliability of the scale in determining SLD (Raman et al, 2020).…”
Section: Content the Current Study Of Cognitive Assessment Of Dyslexiamentioning
confidence: 99%
“…The Woodcock-Johnson Tests of Cognitive Abilities is a valid and reliable instrument for assessing cognitive ability and achievement in children and adults, first introduced in 1977 by Richard Woodcock and Mary E. Bonner Johnson (Woodcock, 1997). In this study, the Woodcock-Johnson IV (WJIV) scale was used to assess children's Reading Comprehension and Language Comprehension as one of the criteria for determining whether a child had Dyslexia, in a study conducted by Sleeman and colleagues on 209 local New Zealand children (Sleeman et al, 2022). Raman and colleagues in order to study the assessment of Dyslexia in children in a multilingual environment, 46 native Indian children aged 8-13 years were selected to participate in the relevant test and Woodcock-Johnsonn III Tests of Academic Achievement were used as an instrument to assess SLD (including Dyslexia) and the results of the study showed the reliability of the scale in determining SLD (Raman et al, 2020).…”
Section: Content the Current Study Of Cognitive Assessment Of Dyslexiamentioning
confidence: 99%
“…In addition, the prevalence of dyslexia from grade 2 to grade 5 was 6.7%, 5.4%, 4.4% and 6.1% respectively, while there was no significant difference in the prevalence among the above four grades. The results of this study show that the Chinese reading ability of children with dyslexia was low in all assessments [38][39][40][41][42][43][44][45] .…”
Section: Prevalence Of Dyslexia In Chinamentioning
confidence: 99%
“…It comprises both screening and individual tests, providing a detailed evaluation of reading abilities (Lindstrom, 2018). The screening index of the STAS identifies students at risk of decoding and spelling difficulties, with those scoring one standard deviation below the mean on decoding tasks across three subtests qualifying for further individual assessment (Sleeman et al, 2022). The individual tests in the STAS provide a more in-depth understanding of an individual's decoding and spelling abilities and can be administered to older children or adults, although they are not standardized for those age groups (Galuschka et al, 2023).…”
Section: Phonological Awareness Assessmentmentioning
confidence: 99%